Design of Sustainable Product Life Cycles - Niemann, Jörg (Springer, 2017)
Product life cycle design – Generating sustainable product life cycles explains the importance of a holistic long-term planning and management approach to reaching a maximum product benefit over the entire life cycle. The paradigm of thinking in product life cycles supports manufacturers in shaping successful products. The book promotes various methods and tools for life cycle management and merges them into an integrated planning approach. In this monograph Europe’s leading academic experts in the field of life cycle management have consolidated their expertise. Readers will learn about different tools and methods for life cycle modelling and digital information support. Industrial examples show how a consistent product data management with closed-loop information cycles enables manufacturers to activate the hidden performance potentials of their products and in their production lines. In this respect Product life cycle design also illustrates the benefits of a networked production including integrated product service systems and innovative business models, and presents methods for evaluating the economic and ecological impacts of life cycle design, highlighting them with practical examples. The book addresses professionals as well as researchers and students from the field of life cycle management. Practitioners and researchers pursuing life cycle excellence will benefit from the comprehensive coverage of methods and various examples from industry.